Interactive Effects of Arbuscular Mycorrhizal Fungi and Rhizobium on Growth and Nutrient Content of Arachis Hypogaea - Kaur, Surinder; Singla, Priyanka; Shruti; Muskaan (International Journal of Sustainable Agricultural Research, 2020)
The present study was intended to investigate individual and interactive effects of Funneliformis mosseae (an arbuscular mycorrhizal fungus) and Rhizobium (a root nodulating bacterium) on growth and yield of groundnut growing under natural conditions. Plants growing in arbuscular mycorrhiza (AM) and/or Rhizobium inoculated soil exhibited superior growth, fitness and yield. Improvement in plant growth due to microbial inoculations had a significant correlation with their response to mycorrhization, relative water content, chlorophyll content, nutrient uptake, and antioxidant activity. The increase in all parameters except N acquisition and protein concentration was significantly higher on the formation of AM than rhizobial inoculation, albeit their combination displayed synergism to uplift metabolism and yield of host legume. Thus, the study indicated that synergistic behavior among microorganisms (AM and Rhizobium) had the most affirmative effects on the growth and harvest index of groundnut variety - TG37A and helped plants to thrive better in soils without chemical fertilizers.